Room temperature weak ferromagnetism in Sn1−xMnxSe2 2D films grown by molecular beam epitaxy - Sining Dong; Xinyu Liu; Xiang Li; Vasily Kanzyuba; Taehee Yoo; Sergei Rouvimov; Suresh Vishwanath; Huili G. Xing; Debdeep Jena; Margaret Dobrowolska; Jacek K. Furdyna (APL Materials, 2016)
We discuss growth and magnetic properties of high-quality two dimensional (2D) Sn1−xMnxSe2 films. Thin films of this 2D ternary alloy with a wide range of Mn concentrations were successfully grown by molecular beam epitaxy. Mn concentrations up to x ≈ 0.60 were achieved without destroying the crystal structure of the parent SnSe2 2D system. Most important, the specimens show clear weak ferromagnetic behavior above room temperature, which should be of interest for 2D spintronic applications.